SINUSOIDAL CELLS AND CYTOKINE RESPONSE IN THE TETRACHLOROMETHANE-INDUCED HEPATOTOXICITY AND AN APPROACH TO ITS CORRECTION - Z. A. Shafigullina; I. G. Danilova; S. Yu. Medvedeva; V. A. Chereshnev; M. T. Abidov (Медицинская иммунология, 2019)
High occurence of liver diseases (toxic, viral hepatitis, liver failure, cirrhosis) requires urgent search of new methods for management of the hepatobiliary diseases. At the present time, the role of immune mechanisms in pathogenesis of diffuse toxic liver damage is not finally clarified. The model of toxic hepatitis induced by carbon tetrachloride (CCl4) is widely known, but this approach allows us to perform complex evaluation and develop the methods for adequate correction of liver disorders in experimental model, which is not always feasible in clinical setting.To design a model of diffuse toxic liver damage, the CCl4 oil solution was used, having been administered intraperitoneally to experimental animals, at a single dose of 50 mg per 100 g body mass. Aiming for correction of toxic liver damage, the injections of aminophthalhydrazide (APH) to experimental animals were carried out intramuscularly at the dose of 2 mg/kg over the terms of experiment. An evaluation of the role of sinusoidal cells (SC) and cytokine production at the local and systemic level were carried out in the model of toxic liver damage caused by CCl4 and its correction by APH treatment. In the course of developing diffuse toxic liver damage induced by CCl4, the production of proinflammatory cytokines TNFα, IL-1α and IL-18 was enhanced at the local level, whereas an increase in TNFα concentration was observed in blood plasma. Following aminophthalhydrazide (APH) administration, the concentrations of proinflammatory cytokines (TNFα and IL-18) decreased at system level, along with locally decreased levels of IL-6 and IFNγ.Changes in the functional state of immunocompetent cells, which include sinusoidal cells (SC), have a significant impact on the development of pathological processes in the liver. The results of our study presume that, over the early periods of toxic impact upon liver tissue, the number of SCs increases both due to influx of blood monocytes and mature macrophages from the peritoneal cavity that enter the injury site directly via mesothelial layer. The SCs provide phagocytosis of damaged hepatocytes and contribute to resolution of the inflammatory process.Modulation of the macrophage activities by APH contributes to increased amounts of SCs at the early stages, and stabilizes their quantities after 2 weeks of APH injections. Change in the numbers of liver SCs during toxic damage affects the production of cytokines. A direct effect of APH upon the SCs may change the production of regulatory factors and compensate the insufficient rate of recovery processes after the toxic damage.